The Senkaku/Diaoyu islands dispute and China’s foreign policy options / Balazs Szanto - Balazs, Szanto (2016)
Since 2012 the East China Sea has seen significant escalation in tensions as Sino-Japanese relations turned for the worse following Tokyo’s nationalisation of the disputed Senkaku/Diaoyu Islands. Despite the growing risk of an armed confrontation between the two major regional military powers (intentionally or accidentally), the security aspects have received limited attention within the academic literature dealing with the dispute. Approaching it from a realist perspective, this research seeks to analyse the security implications of the dispute, primarily focusing on analysing China’s potential course of action under the current circumstances. The key questions this research seeks to determine is whether a military confrontation between China and Japan is likely, and whether there are alternate options for foreign policy that could aver such an outcome. The conclusion of this research is that in the short-term China is likely to follow a delaying strategy as none of the other options are attractive from a rational choice perspective. However, in the medium- to long-term this research sees a significant potential for military confrontation. This is facilitated by Japanese policy eliminating the possibility of a peaceful settlement that would be politically acceptable for China.